Kepok Banana Peel Extract (Musa Paradisiaca) as Antibacterial and Renewable-Biodegradable Surfactant in Liquid Detergent - Putri, Shavyta; Redjeki, Athiek Sri; Nugrahani, Ratri Ariatmi (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
Kepok banana peel contains tannin as antibacterial activity and saponin acts like a surfactant. Detergent is a cleaning agent commonly used by the community. Banana peel is extracted with ethanol solvent to produce antibacterial activity and can be used as a bioadditive. Knowing the antibacterial activity, the extract requires incubation. Because the nature of saponin is the same as surfactant, banana peel extract can be compared with mes surfactant to make liquid detergent. This study was conducted to identify tannin and saponin in banana peel extract, obtain the best banana peel extract yield with the best solvent concentration and the best incubation time for bacterial inhibition, and the best formulation with the addition of extract to the liquid detergent application. The banana peel extraction process with ethanol uses the Ultrasonic Bath Extraction method. The independent variables in this study were the concentration of extraction solvent (50%, 60%, 70%, 80% and 96%) and the formulation of adding banana peel extract (0%, 5%, 10%, 15% and 20%). The best extraction results were obtained with a solvent concentration of 96% which produced a brown liquid with a strong aroma containing tannins and saponins with the best yield of 11.27% and the best antibacterial activity test with a time of 72 hours, then the extract was made into a liquid detergent formulation as a surfactant and compared with MES surfactant so that the best formulation was obtained in formulation F2 (5% banana peel extract 15% methyl ester sulfonate surfactant) and formulation F3 (10% banana peel extract 10% methyl ester sulfonate surfactant).